Genetic-Based Multiresolution Noisy Color Image Segmentation - Yousir, Naeem Th. (Nahrain University College of Engineering Journal, 2010)
Segmentation of a color image composed of different kinds of regions can be a hard problem, namely to compute for an exact texture fields and make a decision of the optimum number of segmentation areas in an image when it contains similar and/or unstationary texture fields. A local novel neighborhood-based segmentation approach is proposed. Genetic algorithm is used in the proposed limited segment-pass optimization process. In this pass, an energy function, which is defined based on Markov Random Fields, is minimized. The proposed system uses an adaptive threshold estimation method for image thresholding in the wavelet domain based on the Generalized Gaussian Distribution (GGD) modeling of sub band coefficients. This method called Normal Shrink is computationally more efficient and adaptive because the parameters required for estimating the threshold depend on sub band data energy that used in the pre-stage of segmentation. A quadtree is utilized to implement the fast clustering segments for multiresolution framework analysis, which enables the use of different strategies at different resolution levels, and hence, the omputation can be accelerated. The experimental results of the proposed segmentation approach are very encouraging